Reduced fat-reduced sodium fermented meat products: a review of reformulation strategies - SANTOS, João Marcos dos; BELLUCCI, Elisa Rafaela Bonadio; CARVALHO, Larissa Tátero; BIS-SOUZA, Camila Vespúcio; LORENZO, Jose Manuel; SILVA-BARRETTO, Andrea Carla da (Food Science and Technology, 2023)
The current research in meat products has been aimed to obtain healthier proposals because of the change in the lifestyle and routine of the population. This new point of view has also changed the industry perspective: they are focusing on reformulation to obtain a portfolio of meat products with a healthier appeal. The process of redefining a traditional formulation can negatively affect the acceptance of the meat product (i.e., taste and appearance). However, researchers reported positive effects in this strategy of reformulations (i.e., added value increase, healthiness, and nutritional enrichment of the product). Sodium reduction, saturated fat reduction, chemical additives reduction, dietary fiber addition, addition of vegetable oils, and probiotic addition are examples of already tested and documented reformulation strategies of fermented meat products. The application of one strategy in a traditional product is a challenge. However, the simultaneous use of two or more strategies is more complex. Thus, the aim of this review was to explain the technological and sensorial benefits and challenges of the application of dietary fibers in meat products submitted to two or more reformulation strategies.